Neurobiology of the major psychoses: a translational perspective on brain structure and function$dthe FOR2107 consortium - Kircher, Tilo; Rietschel, Marcella; Witt, Stephanie (European archives of psychiatry and clinical neuroscience, 2019)
Genetic (G) and environmental (E) factors are involved in the etiology and course of the major psychoses (MP), i.e. major depressive disorder (MDD), bipolar disorder (BD), schizoaffective disorder (SZA) and schizophrenia (SZ). The neurobiological correlates by which these predispositions exert their influence on brain structure, function and course of illness are poorly understood. In the FOR2107 consortium, animal models and humans are investigated. A human cohort of MP patients, healthy subjects at genetic and/or environmental risk, and control subjects (N = 2500) has been established. Participants are followed up after 2 years and twice underwent extensive deep phenotyping (MR imaging, clinical course, neuropsychology, personality, risk/protective factors, biomaterials: blood, stool, urine, hair, saliva). Methods for data reduction, quality assurance for longitudinal MRI data, and (deep) machine learning techniques are employed. In the parallelised animal cluster, genetic risk was introduced by a rodent model (Cacna1c deficiency) and its interactions with environmental risk and protective factors are studied. The animals are deeply phenotyped regarding cognition, emotion, and social function, paralleling the variables assessed in humans. A set of innovative experimental projects connect and integrate data from the human and animal parts, investigating the role of microRNA, neuroplasticity, immune signatures, (epi-)genetics and gene expression. Biomaterial from humans and animals are analyzed in parallel. The FOR2107 consortium will delineate pathophysiological entities with common neurobiological underpinnings (“biotypes”) and pave the way for an etiologic understanding of the MP, potentially leading to their prevention, the prediction of individual disease courses, and novel therapies in the future.
First online: 28 September 2018
Gesehen am 13.11.2019